Virtual environments of teaching learning for training in experimental techniques. Innovation in multidisciplinary groups - Sáez-Pérez, Mª Paz; Kelert, Kerstin; Rodríguez-Navarro, Carlos; Ruiz-Agudo, Encarnación; Ibáñez-Velasco, Aurelia; Cardell-Fernández, Carolina; Blanc-García, María del Rosario; Cultrone, Giuseppe; Bel-Anzue, Pedro (Advances in Building Education, 2021)
In this research, through the development of a teaching innovation project, the aim is to highlight the importance of educational and pedagogical changes that require both the adaptation of teaching to new situations and the possibility of taking advantage of the available resources to be applied in different degrees (master and degree) simultaneously. For this, the innovation experience carried out by a group of professors from the University of Granada who teach subjects in the CiTPA Master, MARA Master and Degree in Conservation and Restoration of Cultural Assets is presented. It addresses the development of unpublished teaching material (videos, manuals for the application of analytical techniques and the use of specialized software, all in a bilingual version), for its integration into different subjects in which it is necessary to make different research techniques known, use of specific software and precise operational activities that are used for the characterization of materials. Competency-based learning through innovation offers students a real and applied experience that has an immediate practical and professional implication, taking advantage of the skills of the new generations. The results, expected in future evaluations, must be analyzed both individually and for the group of subjects, being recognized in advance the good result and the facilities that teamwork, the recognition of skills and the facilities entail in the field of the teacher, the selection of common competences between different subjects and training levels.